Gender and Job Search in Developing Country Labor Markets - Mills, Bradford F. (Wiley, 1997)
Gender discrimination in developing country labor markets raises the concern that women may be unable to find alternative employment following public‐sector job loss. Theoretical and empirical results in this article suggest that, in segmented labor markets, observed unemployment spells may actually be shorter for women than for men. This is a result of the relatively strong incentive wage‐sector discrimination creates for women to accept more readily available, but less‐remunerative, nonwage‐sector positions.